Combined Effect of Methanol Extracts and Essential Oils of Callistemon rigidus (Myrtaceae) and Eucalyptus camaldulensis (Myrtaceae) against Anopheles gambiae Giles larvae (Diptera: Culicidae) - Younoussa, Lame; Kenmoe, Francine; Oumarou, Mallam Kary; Batti, Aurore Christelle Sengue; Tamesse, Joseph Lebel; Nukenine, Elias Nchiwan (International Journal of Zoology, 2020)
Biopesticides from botanicals are nowadays actively encouraged in the mosquito control program because of their low mammalian toxicity, biodegradability, and target specificity. However, leaf methanolic extracts and essential oils of Callistemon rigidus and Eucalyptus camaldulensis were evaluated individually and in combination on third- and fourth-instar larvae of Anopheles gambiae. The extracts were tested individually and in combination at doses of 125, 250, 500, and 1000 ppm while essential oils were applied at 25, 50, 100, and 200 according to the standard protocol of WHO. The commercial insecticide Bi-one tested at the recommended dose of 1000 ppm was used as positive control while the solution of tap water containing 0.5 ml of methanol was used as negative control. The mortality of the larvae was recorded after 24 h postexposure. In the results, 100% mortality of the larvae was recorded with the extracts of C. rigidus and the combinations E50% : C50% and E25% : C75% of the plants as well as positive control (1000 ppm). Similarly, essential oils of the two plants and their combinations caused 100% mortality of the larvae. Among the various combinations of the extracts and essential oils, only the combination E75% : C25% of essential oils presented a synergistic effect. Therefore, the essential oil combination (E75% : C25%) of the plants E. camaldulensis and C. rigidus is recommended in order to promote the its use in the form of natural biocide in the implementation of effective insect controls against the mosquito larvae, vector of malaria.